2002
DOI: 10.1086/341565
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Responses to Epitopes of the Major Surface Glycoprotein ofPneumocystis jiroveciDiffer in Human Immunodeficiency Virus–Infected and Uninfected Persons

Abstract: The major surface glycoprotein (Msg) of Pneumocystis jiroveci (P. jiroveci) is important in the immunopathogenesis of Pneumocystis pneumonia (PcP), but is difficult to study in humans. We generated 3 overlapping recombinant Msg fragments (MsgA, MsgB and MsgC), and analyzed their reactivity with serum samples from 95 healthy blood donors and 94 human immunodeficiency virus (HIV)-infected persons. Reactivity to the Msg fragments varied with HIV infection and prior episodes of PcP but not with geographic origin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 43 publications
3
68
2
1
Order By: Relevance
“…Although these studies have demonstrated that the prevalence of seroreactivity is high and varies by geographic location, assays using crude extracts have produced conflicting results regarding seroprevalence in surveys of healthy and immunocompromised hosts and generally fail to distinguish active infection from previous exposure, and thus these reagents have been of limited clinical use. With the development of recombinant Pneumocystis antigens, more recent studies investigating the utility of specific antigens for serologic studies are producing promising results in this area (22,52,173,203).…”
Section: Humoral Responsementioning
confidence: 99%
“…Although these studies have demonstrated that the prevalence of seroreactivity is high and varies by geographic location, assays using crude extracts have produced conflicting results regarding seroprevalence in surveys of healthy and immunocompromised hosts and generally fail to distinguish active infection from previous exposure, and thus these reagents have been of limited clinical use. With the development of recombinant Pneumocystis antigens, more recent studies investigating the utility of specific antigens for serologic studies are producing promising results in this area (22,52,173,203).…”
Section: Humoral Responsementioning
confidence: 99%
“…The diminished humoral responses in HIV-infected individuals upon vaccination with carbohydrate antigens and T-independent antigens, such as the pneumococcal vaccine, may be due to a deficit in a particular subset of memory B cells, such as IgM memory cells (26) Several studies of HIV ϩ patients focus on recall responses to antigens or pathogens against which study participants have been vaccinated (37,61) or to antigens that they are not likely to be naturally exposed (i.e., tetanus toxoid) (13,26). The present study explores humoral responses to a naturally acquired, ubiquitous organism to which most humans (9,42,51) and nonhuman primates (10,30) have been continuously exposed before and after HIV or SHIV infection. The maintenance of the Pneumocystis-KEX1-specific antibody responses and B-cell memory during SHIV-induced immunosuppression in monkeys that had high Pneumocystis humoral immunity preinfection suggests that responses to this antigen were not significantly affected by SHIV infection.…”
Section: Test) (D) Monkeys That Remained Pcmentioning
confidence: 99%
“…There is a high frequency of Pneumocystis-specific seroprevalence in immunocompetent adults (1,9), as well as in nonhuman primates (11,30), suggesting the persistence of serological memory or Pneumocystis-specific, long-lived plasma cells in response to natural Pneumocystis exposure. Antibodies to the Pneumocystis endoprotease kexin (KEX1) may be particularly important, because immune responses to Pneumocystis KEX1 have been associated with control of Pneumocystis infection in immunosuppressed murine models (62,63).…”
mentioning
confidence: 99%
“…We and others have generated recombinant fragments of Msg for use in immunological assays (2,7,8,29). The carboxyl terminus of Msg, which we call MsgC, is the most antigenic fragment of Msg and has received much attention.…”
mentioning
confidence: 99%